Penerapan Metode Brown Gibson Dalam Menentukan Penerima Kalpataru - Harahap, Yudi Arta (Forum Kerjasama Pendidikan Tinggi (FKPT), 2020)
The implementation of the Brown Gibson method in determining kalpataru recipients is done by choosing an alternative that follows a series of stages of activities given and criteria that are suitable for kalpataru recipients. The problem faced by the selection team or the Kalpataru consideration board is how to determine the Kalpataru recipient from a number of alternatives that have their respective strengths and weaknesses so that they are not well targeted to provide the best value for analysis.This system is a Decision Support System (SPK) which was built using the Brown Gibson method and designed using Microsoft Visual Studio 2008 and using a Microsoft Access database. For data processing will be carried out by a selection team or board of judges from the Office of Environment of North Sumatra Province by entering the Kalpataru recipient value data, the system will perform calculations according to the principle of the Brown Gibson method which ultimately results in a ranking that can help the selection team in comparing ranking obtained. The system created has been able to determine who is entitled to be the recipient of the Kalpataru award as expected.